THE IMPACT OF PERCEIVED ORGANIZATIONAL SUPPORT ON REDUCING WORK-RELATED STRESS - Maryam Hassan Kasad; Amal Jaber Fazaa (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to examine the effect of Perceived Organizational Support (POS) on reducing employee job-related stress by analyzing the Pearson correlation between employees’ perceptions of organizational concern for their well-being and appreciation of their contributions and their experienced stress levels. Method: A descriptive-quantitative research design was employed, utilizing a structured questionnaire administered to 348 employees at Maysan University, Iraq. Collected data were analyzed using SPSS version 26 to determine the strength and significance of correlations. Results: Findings reveal a significant negative Pearson correlation between POS and job-related stress, indicating that higher levels of organizational support are associated with lower employee stress, enhanced mental well-being, and improved work performance. Novelty: This research contributes new empirical evidence from the higher-education sector in Iraq, a context that remains underrepresented in POS–stress literature, highlighting the critical role of organizational support in promoting employee psychological health and institutional productivity.